Acrylic acid monomer containing carboxylic acid group, conductive adhesive for chip packaging and preparation method of conductive adhesive
By using acrylic monomers and other components containing carboxylic acid groups in the conductive glue to form carbon-carbon covalent bonds, the problem of degradation of conductivity caused by diffusion of short-chain dicarboxylic acids is solved, and the stability of the conductive glue is improved. Durability enhances its performance after cooking in a pressure cooker.
Patent Information
- Application Number
- CN202411367068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The diffusion of short-chain dicarboxylic acid in conductive glue leads to a decrease in conductivity, affecting the reliability and mechanical properties of the device, especially in humid or harsh environments, increasing the risk of electrochemical corrosion, reducing the stability and durability of the conductive glue.
The acrylic monomer containing carboxylic acid groups is prepared by esterification of unsaturated alcohol and acid anhydride to form an unsaturated carboxylic acid ester, combining polybutadiene dimethacrylate, polybutadiene epoxy resin, and acrylate monomer The conductive adhesive for chip packaging is prepared by polymerizing the formation of carbon-carbon covalent bonds to reduce the diffusion of carboxylic acid groups.
It significantly improves the overall stability and durability of the conductive glue, enhances its performance after cooking with pressure cooker, reduces the decline in conductive properties, and extends the service life of the device.
Smart Images

Figure CN119241364A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive adhesive preparation, and particularly relates to an acrylic monomer containing a carboxylic acid group and a conductive adhesive for chip packaging and a preparation method thereof. Background Art
[0002] Conductive adhesive, as an advanced adhesive material in the modern electronic manufacturing industry, is gradually replacing traditional lead-tin soldering technology, providing a more environmentally friendly and efficient electronic component interconnection solution. This material is made of a resin matrix, a curing agent, a conductive filler, a diluent and other additives, and integrates many advantages: environmental friendliness, low curing temperature, protection of sensitive components, high line resolution and fast curing, which greatly shortens the production cycle and improves efficiency. As the core component of conductive adhesive, silver powder not only gives it excellent conductive properties, but also reduces thermal stress and ensures product reliability by enhancing mechanical strength and wear resistance, as well as excellent thermal stability in high temperature environments. The environmental protection characteristics of silver powder meet the green development needs of the modern manufacturing industry and avoid the use of harmful solders. Especially in automated production, the versatility of silver powder enables it to be mixed with other fillers to create a variety of conductive adhesive formulas to meet a wide range of application needs.
[0003] Conductive adhesives are composed of polymer binders and silver flakes coated with a thin layer of organic lubricant. This layer of lubricant, mainly composed of fatty acids such as stearic acid, not only plays a vital role in the dispersion of silver flakes in the adhesive and the rheological properties of the adhesive, but also forms silver salt complexes on the silver surface, enhancing the dispersion of silver flakes. However, since this layer of lubricant is electrically insulating, it will hinder the conductive properties of the conductive adhesive. In order to optimize the conductivity, it is necessary to partially or completely remove or replace this layer of organic lubricant during the curing process of the conductive adhesive. Short-chain dicarboxylic acids are ideal lubricant removers due to their high affinity for silver and strong acidity. Only an appropriate amount of short-chain dicarboxylic acids can significantly improve the conductivity of the conductive adhesive, promote electron tunneling and transmission between silver flakes, and achieve closer inter-flake contact, thereby optimizing the conductive performance. During the application of the conductive adhesive, the short-chain dicarboxylic acids promote electron transmission between silver flakes by interacting with the silver salt complexes on the surface of the silver powder, thereby improving the conductive properties of the conductive adhesive. However, over time, the short-chain dicarboxylic acids in the conductive adhesive may diffuse. This diffusion may lead to the formation of a new insulating layer on the surface of the silver flakes, which will hinder the flow of electrons and gradually reduce the conductivity. In addition, the diffusion phenomenon may also reduce the thermal conductivity of the conductive adhesive, affect its heat dissipation efficiency, cause local temperature rise, and adversely affect the performance and service life of the device. At the same time, the mechanical properties of the conductive adhesive, such as its elastic modulus and tensile strength, may be reduced due to diffusion, which may cause mechanical failure of the device under mechanical stress. A new interface layer may form at the interface between the conductive adhesive and the electronic components, which may affect the stability of the device's electrical connection and signal transmission. In humid or harsh environments, the diffused dicarboxylic acid may increase the hygroscopicity of the conductive adhesive, leading to conductivity fluctuations and the risk of electrochemical corrosion. Especially in applications with strict requirements on stability, the long-term diffusion process may weaken the reliability of the conductive adhesive and increase the possibility of device failure. Summary of the invention
[0004] To solve the above-mentioned technical problems, the present invention provides a kind of acrylic acid monomer containing carboxylic acid group, by preparing novel unsaturated carboxylic acid ester by esterification reaction of unsaturated alcohol and monobasic / dibasic acid anhydride.Wherein, unsaturated alcohol is a kind of alcohol organic compound containing at least one carbon-carbon double bond (olefinic bond), and its molecular structure contains hydroxyl (-OH) and is connected with carbon atom, including but not limited to: allyl alcohol, 2-butene-1-ol, 2-pentene-4-ol, 2-methyl-2-butene-1-ol, 3-hexene-1-ol, 2-ethylhexene-1-ol, 2-methyl-2-pentene-4-ol, 3-methyl-3-pentene-1-ol, 2-heptene-1-ol, 2-octen-1-ol, 2-dodecene-1-ol, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate (HEMA) and 2-hydroxypropyl methacrylate (HPMA) etc. The acid anhydride includes, but is not limited to, phthalic anhydride, tetrahydrophthalic anhydride, 4-methylphthalic anhydride, itaconic anhydride, biphenyl anhydride, phenylsuccinic anhydride, 3,3,4,4-biphenyltetracarboxylic anhydride, pyromellitic anhydride, 1,8-naphthalene dicarboxylic anhydride, bromomaleic anhydride, 2,3-dichloromaleic anhydride, 3,3,4,4-benzophenonetetracarboxylic anhydride, 3-nitrophthalic anhydride, 2-dodecene-1-yl-succinic anhydride, hexafluoroglutaric anhydride, 2,3-dimethylmaleic anhydride, homophthalic anhydride, tetrabromophthalic anhydride, bicyclo[2,2,2 ]Oct-7-ene 2,3,5,6-tetracarboxylic anhydride, 3-fluorophthalic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, methacrylic anhydride, citraconic anhydride, hexahydro-4-methylphthalic anhydride, maleic anhydride, 2,3-diphenylmaleic anhydride, tetrafluorophthalic anhydride, 1,2-cyclohexanedicarboxylic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, glutaric anhydride, bromomaleic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 1,2,4-benzenetricarboxylic anhydride, 1,2,4,5-pyromellitic anhydride, 1,2,4-benzenetricarboxylic anhydride, etc. The preparation method of the monomer is generally to mix one molar equivalent of anhydride with one or two molar equivalents of unsaturated alcohol in the presence of a small amount of tertiary amine (such as triethylamine, tripropylamine, etc.), heat to 80-90°C and stir until a clear solution is formed, and the progress of the reaction can be determined by infrared monitoring of the change in the absorption band of the cyclic anhydride. After the reaction is completed, the product needs to be purified to ensure that the desired unsaturated carboxylic acid ester is obtained.
[0005] The present invention also provides a conductive adhesive for chip packaging containing an acrylic acid monomer having a carboxylic acid group, comprising the following components in percentage by mass:
[0006] Polybutadiene dimethacrylate 2.5-20%;
[0007] Polybutadiene epoxy resin 2-5%;
[0008] Acrylate monomer 7-15%;
[0009] 0-2% of acrylic acid monomer containing carboxylic acid group;
[0010] Bismaleimide 0-5%;
[0011] Coupling agent 0.1~1%;
[0012] Free radical initiator 0.5-4%;
[0013] Epoxy curing agent 0.5-4%;
[0014] Inhibitor 0.01~0.8%;
[0015] Fumed silica 0.5-2%;
[0016] Silver powder filler 70-80%.
[0017] The polybutadiene dimethacrylate is selected from liquid hydrogenated polybutadiene or non-hydrogenated polybutadiene modified by (meth)acrylic acid, such as any one or more of CN301, CN302, CN307, FSP5494, etc.
[0018] The polybutadiene epoxy resin is selected from any one or more of D-17 epoxy resin, 2000 epoxy resin, 62000 epoxy resin, PB4700, PB3600, JP200 and the like.
[0019] The acrylate monomer is selected from cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, methoxycyclodecatriene (meth)acrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, tetraethylene glycol diacrylate, tricyclodecane dimethanol diacrylate, alkoxylated hexanediol diacrylate, bisphenol A alkylene oxide modified di(meth)acrylate. any one or more of 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane and 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane.
[0020] The acrylic monomer containing a carboxylic acid group is selected from the monomers prepared by the above method.
[0021] The bismaleimide is selected from any one or more of 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide, m-phenylenedimaleimide, 2,2'-bis[4-(4-maleimidephenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylenedimaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, etc.
[0022] The coupling agent is selected from one or a mixture of γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriisopropoxysilane and γ-methacryloxymethyldimethoxysilane.
[0023] The free radical initiator is selected from any one or more of ketone peroxide, diacyl peroxide, peroxyester, peroxyketal and peroxycarbonate.
[0024] The epoxy curing agent is selected from dicyandiamide, solid aromatic amine, aromatic urea, or imidazole curing agent.
[0025] The polymerization inhibitor is selected from any one or more of methylhydroquinone, hydroquinone, 2,2-methylene-bis(4-methyl-6-tert-butylphenol), catechol, hydroquinone monomethyl ether, mono-tert-butylhydroquinone, 2,5-dichloro-1,4-benzoquinone and the like.
[0026] The fumed silica is selected from one or more of TS720, TS530, TS612, H15, H18, H17, H20, H30, R202, R972, QS-10, QS-10LS, QS-102, CP-102, QS-20, MT-10, MT-10C, and DM-10.
[0027] The silver powder filler preferably has a specific surface area of less than 1 m 2 / g, density 2-6g / cc, the silver powder morphology is preferably one or more of flake, spherical, dendritic and irregular shapes.
[0028] A method for preparing a conductive adhesive for chip packaging containing an acrylic acid monomer having a carboxylic acid group, comprising the following steps:
[0029] (1) The acrylic acid ester monomer and the fumed silica are put into a toothed disk stirrer in proportion and stirred at high speed to prepare a semi-finished product containing fumed silica.
[0030] (2) The semi-finished product containing gas silicon in step (1), polybutadiene dimethacrylate, polybutadiene epoxy resin, acrylic monomer containing carboxylic acid group and bismaleimide are put into a planetary mixer according to proportion at 5-35° C. and mixed for 45-90 minutes, and then a coupling agent, a free radical initiator and an epoxy curing agent are added and mixed at room temperature for 60 minutes to form a uniform primary mixture.
[0031] (3) Adding silver powder fillers to the primary mixture obtained in step (2), mixing at room temperature for 60 minutes, and applying vacuum degassing to obtain a conductive adhesive.
[0032] The invention provides a conductive adhesive for chip packaging containing an acrylic acid monomer containing a carboxylic acid group, which reduces the diffusion of the carboxylic acid group by forming a carbon-carbon covalent bond after polymerization, thereby improving the overall stability and durability of the conductive adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a C+TScan result diagram of the device made of the conductive adhesive in Example 4 of the present invention after being treated under MSL1 conditions.
[0034] Figure 2 This is a C+T Scan result diagram of the device made of the conductive adhesive in Example 1 after being processed under MSL1 conditions. DETAILED DESCRIPTION
[0035] Example 1
[0036] Synthesis of acrylic acid monomer 1 containing carboxylic acid groups
[0037] 21.81 g (0.1 mol) of symmetric pyromellitic anhydride was weighed into a flask, and 28.83 g (0.2 mol) of 4-hydroxybutyl acrylate was added together with 0.1 ml of triethylamine. The mixture was stirred and heated at 90° C. for 6 hours, during which a clear solution was obtained, at which time the infrared spectrum of the product showed that the anhydride absorption band disappeared. This product was named acrylic acid monomer 1 containing a carboxylic acid group.
[0038] Example 2
[0039] Synthesis of acrylic monomer 2 containing carboxylic acid groups
[0040] 32.22 g (0.1 mol) of 3,3',4,4'-benzophenonetetracarboxylic dianhydride was weighed into a flask, and 28.83 g (0.2 mol) of 4-hydroxybutyl acrylate was added together with 0.1 ml of triethylamine. The mixture was stirred and heated at 90°C for 6 hours, during which a clear solution was obtained. The infrared spectrum of the product at this time showed that the anhydride absorption band disappeared. This product was named acrylic monomer 2 containing a carboxylic acid group.
[0041] Example 3
[0042] Synthesis of acrylic monomer 3 containing carboxylic acid groups
[0043] 14.81 g (0.1 mol) of phthalic anhydride was weighed into a flask, and 14.41 g (0.1 mol) of 4-hydroxybutyl acrylate was added together with 0.1 ml of triethylamine. The mixture was stirred and heated at 90° C. for 6 hours, during which a clear solution was obtained. The infrared spectrum of the product at this time showed that the anhydride absorption band disappeared. This product was named acrylic monomer 3 containing a carboxylic acid group.
[0044] Example 4
[0045] A method for preparing a conductive adhesive for chip packaging containing an acrylic monomer containing a carboxylic acid group comprises the following steps:
[0046] (1) 11 parts by weight of isobornyl methacrylate and 1 part by weight of TS720 were weighed in a proportion and put into a toothed disk stirrer and stirred at high speed to prepare a semi-finished product containing gas silicon.
[0047] (2) The semi-finished product containing gas silicon, 7.9 parts by mass of CN301, 2 parts by mass of PB3600, 1 part by mass of acrylic monomer 1 containing a carboxylic acid group, and 1 part by mass of 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide were placed in a planetary mixer in proportion and mixed for 90 minutes at room temperature, and then 0.1 part by mass of γ-methacryloxypropyltrimethoxysilane, 0.5 part by mass of 1,1-bis(tert-amylperoxy)cyclohexane, and 0.5 part by mass of dicyandiamide were added and mixed for 60 minutes at room temperature to form a uniform primary mixture.
[0048] (3) Finally, 75 parts by weight of flaky silver powder is added to the primary mixture prepared above in batches and fully stirred, vacuum degassed, and packaged to obtain a conductive adhesive.
[0049] Example 5
[0050] A method for preparing a conductive adhesive for chip packaging containing an acrylic monomer containing a carboxylic acid group comprises the following steps:
[0051] (1) 11 parts by weight of isobornyl methacrylate and 1 part by weight of TS720 were weighed in a proportion and put into a toothed disk stirrer and stirred at high speed to prepare a semi-finished product containing gas silicon.
[0052] (2) The semi-finished product containing gas silicon, 7.9 parts by mass of CN301, 2 parts by mass of PB3600, 1 part by mass of acrylic monomer 2 containing a carboxylic acid group, and 1 part by mass of 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide were placed in a planetary mixer according to the proportions at room temperature and mixed for 90 minutes. Then, 0.1 part by mass of γ-methacryloxypropyltrimethoxysilane, 0.5 part by mass of 1,1-bis(tert-amylperoxy)cyclohexane, and 0.5 part by mass of dicyandiamide were added and mixed for 60 minutes at room temperature to form a uniform primary mixture.
[0053] (3) Finally, 75 parts by weight of flaky silver powder is added to the primary mixture prepared above in batches and fully stirred, vacuum degassed, and packaged to obtain a conductive adhesive.
[0054] Example 6
[0055] A method for preparing a conductive adhesive for chip packaging containing an acrylic monomer containing a carboxylic acid group comprises the following steps:
[0056] (1) 11 parts by weight of isobornyl methacrylate and 1 part by weight of TS720 were weighed in a proportion and put into a toothed disk stirrer and stirred at high speed to prepare a semi-finished product containing gas silicon.
[0057] (2) The semi-finished product containing gas silicon, 7.9 parts by mass of CN301, 2 parts by mass of PB3600, 1 part by mass of acrylic monomer 3 containing a carboxylic acid group, and 1 part by mass of 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide were put into a planetary mixer according to the proportion and mixed for 90 minutes at room temperature, and then 0.1 part by mass of γ-methacryloxypropyltrimethoxysilane, 0.5 part by mass of 1,1-bis(tert-amylperoxy)cyclohexane, and 0.5 part by mass of dicyandiamide were added and mixed for 60 minutes at room temperature to form a uniform primary mixture.
[0058] (3) Finally, 75 parts by weight of flaky silver powder is added to the primary mixture prepared above in batches and fully stirred, vacuum degassed, and packaged to obtain a conductive adhesive.
[0059] Comparative Example 1
[0060] Comparative Example 1 The preparation method comprises the following steps:
[0061] (1) 11 parts by weight of isobornyl methacrylate and 1 part by weight of TS720 were weighed in a proportion and put into a toothed disk stirrer and stirred at high speed to prepare a semi-finished product containing gas silicon.
[0062] (2) The semi-finished product containing gas silicon, 7.9 parts by mass of CN301, 2 parts by mass of PB3600, 1 part by mass of adipic acid, and 1 part by mass of 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide were put into a planetary mixer according to the proportion and mixed for 90 minutes at room temperature, and then 0.1 parts by mass of γ-methacryloxypropyltrimethoxysilane, 0.5 parts by mass of 1,1-bis(tert-amylperoxy)cyclohexane, and 0.5 parts by mass of dicyandiamide were added and mixed for 60 minutes at room temperature to form a uniform primary mixture;
[0063] (3) Finally, 75 parts by weight of flaky silver powder is added to the primary mixture prepared above in batches and fully stirred, vacuum degassed, and packaged to obtain a conductive silver paste.
[0064] Comparative Example 2
[0065] Comparative Example 2 The preparation method comprises the following steps:
[0066] (1) 11 parts by weight of isobornyl methacrylate and 1 part by weight of TS720 were weighed in a proportion and put into a toothed disk stirrer and stirred at high speed to prepare a semi-finished product containing gas silicon.
[0067] (2) The semi-finished product containing gas silicon, 7.9 parts by mass of CN301, 2 parts by mass of PB3600, 1 part by mass of glutaric acid, and 1 part by mass of 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide were placed in a planetary mixer according to the proportion and mixed for 90 minutes at room temperature, and then 0.1 part by mass of γ-methacryloxypropyltrimethoxysilane, 0.5 part by mass of 1,1-bis(tert-amylperoxy)cyclohexane, and 0.5 part by mass of dicyandiamide were added and mixed for 60 minutes at room temperature to form a uniform primary mixture.
[0068] (3) Finally, 75 parts by weight of flaky silver powder is added to the primary mixture prepared above in batches and fully stirred, vacuum degassed, and packaged to obtain a conductive silver paste.
[0069] The conductive adhesives prepared in the embodiments and comparative examples were subjected to the following measurements:
[0070] a. Viscosity measurement: Viscosity was measured using a Brookfield RVDV viscometer equipped with an S14 spindle at a temperature of 25°C and a rotation speed of 5 rpm.
[0071] b. Volume resistivity: Prepare the sample according to ASTM D257 standard, and place two parallel 3M magic tapes 4mm apart along the length of a standard size 25.4mm×76.2mm slide. Then place a small amount of the glue to be tested between the two tapes. Use a clean slide held at a 45° angle to evenly squeeze the adhesive into the 4mm space between the tapes. After squeezing, tear off the tape and bake the slide in an oven preheated to 175°C for 1.5 hours. After curing is complete, remove the sample and measure its volume resistivity using the standard online four-probe method. Each type of glue was tested 5 times and the average value was recorded.
[0072] c. Chip bonding strength test: According to MIL-STD-883 standard, the Dage4000 series thrust tester was used for testing. The bonded chip size is 2mm×2mm. After bonding to the metal frame, it was cured in an oven at 175°C for 1.5 hours. Eight samples were prepared for each embodiment and comparative example to test the initial shear strength and the shear strength after autoclave cooking.
[0073] d. Referring to the method of J-STD-020C standard, the conductive adhesives of Example 4 and Comparative Example 1 were made into devices, and ultrasonic scanning imaging was performed after treatment under MSL1 conditions.
[0074]
[0075] Figure 1 This is a C+T Scan result diagram of the device of Example 4 after being processed using the MSL1 condition.
[0076] Figure 2 This is a C+T Scan result diagram of the device of Comparative Example 1 after being processed using MSL1 conditions.
[0077] The experimental results of the new monomer on the viscosity and resistance to autoclave cooking in the conductive adhesive formula show that the introduction of the new monomer has little effect on the viscosity of the formula, which can be verified from the viscosity data of the embodiment and the comparative example, the viscosity values of the two are similar. Further experiments show that after autoclave cooking, the shear strength of the embodiment decreases by 10-20%, while the decrease of the comparative example is as high as 50-60%. This significant difference reveals that the new monomer forms carbon-carbon covalent bonds through polymerization, effectively restricting the diffusion of carboxylic acid groups, thereby enhancing the resistance to autoclave cooking of the conductive adhesive.
[0078] In addition, the volume resistivity of the embodiment and the comparative example is close, indicating that the addition of the new monomer does not significantly change the conductive properties of the conductive adhesive. In order to further verify the effect of the new monomer on the stability of the conductive adhesive, we made devices with the conductive adhesives of Example 4 and Comparative Example 1, and performed ultrasonic scanning imaging under MSL1 conditions. The result of C+T Scan clearly shows that the device of Example 4 did not show stratification after treatment, while the device of Comparative Example 1 showed obvious stratification. This result shows that the addition of the new monomer significantly improves the overall stability and durability of the conductive adhesive, which is of great significance for improving the long-term reliability of electronic devices.
[0079] In summary, the introduction of the new monomer has little effect on the viscosity of the conductive adhesive, but can significantly improve its resistance to autoclave cooking and long-term reliability, which has a potential positive impact on the application of conductive adhesives in the field of electronic packaging.
[0080] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions may occur depending on design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An acrylic acid monomer containing a carboxylic acid group, characterized in that: The acrylic acid monomer is an unsaturated carboxylic acid ester obtained by esterification reaction of unsaturated alcohol and monobasic / dibasic acid anhydride.
2. The acrylic acid monomer containing a carboxylic acid group according to claim 1, characterized in that The unsaturated alcohol is an alcohol organic compound containing at least one carbon-carbon double bond, including but not limited to: allyl alcohol, 2-butene-1-ol, 2-pentene-4-ol, 2-methyl-2-butene-1-ol, 3-hexene-1-ol, 2-ethylhexene-1-ol, 2-methyl-2-pentene-4-ol, 3-methyl-3-pentene-1-ol, 2-heptene-1-ol, 2-octen-1-ol, 2-dodecene-1-ol, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate; The acid anhydride includes, but is not limited to, phthalic anhydride, tetrahydrophthalic anhydride, 4-methylphthalic anhydride, itaconic anhydride, biphenyl anhydride, phenylsuccinic anhydride, 3,3,4,4-biphenyltetracarboxylic anhydride, pyromellitic anhydride, 1,8-naphthalene dicarboxylic anhydride, bromomaleic anhydride, 2,3-dichloromaleic anhydride, 3,3,4,4-benzophenonetetracarboxylic anhydride, 3-nitrophthalic anhydride, 2-dodecene-1-yl-succinic anhydride, hexafluoroglutaric anhydride, 2,3-dimethylmaleic anhydride, homophthalic anhydride, tetrabromophthalic anhydride, bicyclo[2,2,2 ]Oct-7-ene 2,3,5,6-tetracarboxylic anhydride, 3-fluorophthalic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, methacrylic anhydride, citraconic anhydride, hexahydro-4-methylphthalic anhydride, maleic anhydride, 2,3-diphenylmaleic anhydride, tetrafluorophthalic anhydride, 1,2-cyclohexanedicarboxylic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, glutaric anhydride, bromomaleic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 1,2,4-benzenetricarboxylic anhydride, 1,2,4,5-pyromellitic anhydride, 1,2,4-benzenetricarboxylic anhydride.
3. A method for preparing an acrylic acid monomer containing a carboxylic acid group, characterized in that: In the presence of a tertiary amine, one molar equivalent of anhydride is mixed with one or two molar equivalents of an unsaturated alcohol, heated to 80-90°C and stirred until a clear solution is formed.
4. A conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group, characterized in that: The following components are included in mass percentage: Polybutadiene dimethacrylate 2.5-20%; Polybutadiene epoxy resin 2-5%; Acrylate monomer 7-15%; 0-2% of the acrylic acid monomer containing a carboxylic acid group as claimed in claim 1; Bismaleimide 0-5%; Coupling agent 0.1~1%; Free radical initiator 0.5-4%; Epoxy curing agent 0.5-4%; Inhibitor 0.01~0.8%; Fumed silica 0.5-2%; Silver powder filler 70-80%.
5. The conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group according to claim 4, characterized in that: The polybutadiene dimethacrylate is selected from liquid hydrogenated polybutadiene or non-hydrogenated polybutadiene modified by methacrylic acid; the polybutadiene epoxy resin is selected from any one or more of D-17 epoxy resin, 2000 epoxy resin, 62000 epoxy resin, PB4700, PB3600 and JP200.
6. The conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group according to claim 4, characterized in that: The acrylate monomer is selected from cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, methoxycyclodecatriene (meth)acrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, tetraethylene glycol diacrylate, tricyclodecane dimethanol diacrylate, alkoxylated hexanediol diacrylate, bisphenol A alkylene oxide modified di(meth)acrylate. Any one or more of 2,2-bis(4-(meth)acryloxyphenyl)propane, 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane and 2,2-bis(4-(meth)acryloxypolyethoxyphenyl)propane.
7. The conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group according to claim 4, characterized in that: The bismaleimide is selected from any one or more of 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide, m-phenylenedimaleimide, 2,2'-bis[4-(4-maleimidephenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylenedimaleimide, and 1,6'-bismaleimide-(2,2,4-trimethyl)hexane.
8. The conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group according to claim 4, characterized in that: The coupling agent is selected from one or a mixture of γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriisopropoxysilane and γ-methacryloxymethyldimethoxysilane; The free radical initiator is selected from any one or more of ketone peroxide, diacyl peroxide, peroxyester, peroxyketal and peroxycarbonate; The epoxy curing agent is selected from dicyandiamide, solid aromatic amine, aromatic urea, or imidazole curing agent; The polymerization inhibitor is selected from any one or more of methyl hydroquinone, hydroquinone, 2,2-methylene-bis(4-methyl-6-tert-butylphenol), catechol, hydroquinone monomethyl ether, mono-tert-butyl hydroquinone, and 2,5-dichloro-1,4-benzoquinone; The fumed silica is selected from one or more of TS720, TS530, TS612, H15, H18, H17, H20, H30, R202, R972, QS-10, QS-10LS, QS-102, CP-102, QS-20, MT-10, MT-10C, and DM-10.
9. The conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group according to claim 4, characterized in that: The specific surface area of the silver powder filler is less than 1m 2 / g, density 2-6g / cc; the silver powder morphology is one or more of flake, spherical, dendritic and irregular shapes.
10. A method for preparing a conductive adhesive for chip packaging containing an acrylic monomer having a carboxylic acid group, characterized in that: The following steps are involved: (1) acrylic acid ester monomer and fumed silica are put into a toothed disk stirrer in proportion and stirred at high speed to prepare a semi-finished product containing fumed silica; (2) adding the semi-finished product containing gas silicon in step (1), polybutadiene dimethacrylate, polybutadiene epoxy resin, acrylic monomer containing carboxylic acid group, and bismaleimide into a planetary mixer according to proportion at 5-35° C. and mixing for 45-90 minutes, and then adding a coupling agent, a free radical initiator, and an epoxy curing agent and mixing for 60 minutes at room temperature to form a uniform primary mixture; (3) Adding silver powder fillers to the primary mixture obtained in step (2), mixing at room temperature for 60 minutes, and applying vacuum degassing to obtain a conductive adhesive.
